Communal invalidation of young adults with co-occurring substance abuse and mental health issues. Issue 6 (3rd July 2019) - Semb, Randi; Tjora, Aksel; Borg, Marit
Abstract: This study explores how young adults with co-occurring substance abuse and mental health issues experience the challenges of belonging to their local communities. The data were generated through qualitative in-depth interviews with seven young adult service users, six of whom were interviewed twice. The qualitative data analysis resulted in three overarching themes: the need to accept one's own life and the structures surrounding it; being caught between conflicting social worlds; and moral fumbling in choices and actions. Using an empirical study, we suggest that a process of 'communal invalidation' operates through which young adults in the community are socially defined as inadequate. This invalidation serves as a formidable barrier to their recovery.